1994
DOI: 10.1891/0886-6708.9.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Diagnostic Efficacy of Parents’ Reports Regarding Children’s Exposure to Marital Aggression

Abstract: Mothers, fathers, and 8- to 11-year-old children from 181 two-parent families independently reported on the occurrence of husband-to-wife physical aggression and wife-to-husband physical aggression; parents additionally indicated whether the child had been witness to the aggression. First this study examined interspousal agreement regarding whether parents have been physically aggressive toward one another and whether the child has witnessed interparental physical aggression. There was moderate agreement betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 0 publications
1
67
0
Order By: Relevance
“…Almost all of the studies reported above relied on mothers' reports of their children's problems. As pointed out earlier, O'Brien, et al(1994) have shown that many parents report their children are unaware of violence between the adults when the children, in fact, report awareness of it. Studies that rely on the reports of only parents to define witnessing may incorrectly classify significant numbers of children as non-witnesses.…”
Section: Research Methodologiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Almost all of the studies reported above relied on mothers' reports of their children's problems. As pointed out earlier, O'Brien, et al(1994) have shown that many parents report their children are unaware of violence between the adults when the children, in fact, report awareness of it. Studies that rely on the reports of only parents to define witnessing may incorrectly classify significant numbers of children as non-witnesses.…”
Section: Research Methodologiesmentioning
confidence: 89%
“…Reports by children and by adults of their childhood experiences suggest that parents may severely underestimate the degree to which their children are exposed to the violence. For example, O'Brien, John, Margolin and Erel (1994) found that one in four of the children in a community-based sample reported seeing violence used by one parent against another. Over a third (36%) of these children reporting seeing violence used by fathers against mothers when at least one parent reported no violence occurred or that their children had not seen such events.…”
Section: Discrepancies In Reportsmentioning
confidence: 99%
“…The best way to learn about them is to ask directly those potentially involved. Selfreports remain among the most reliable methods used also to disclose youngsters' victimization, including bullying in school (O'Brien et al, 1994;Baldry, 1998) but they should be validated, where possible, from other sources (parents, social welfare records, peers or teacher).…”
Section: Animal Abuse Bullying and Family Violencementioning
confidence: 99%
“…Studies have also suggested significant discrepancies on parent estimates of exposure of children to partner violence and children reports (Dobash & Dobash, 1984;Hughes, Parkinson, & Vargo, 1989;O'Brien, John, Margolin, & Erel, 1994). Parents tend to underestimate the frequency of child exposure.…”
Section: Discrepant Reports On Violencementioning
confidence: 99%